On the relation between Seyfert 2 accretion rate and environment at z < 0.1 - Coldwell Lloveras, Georgina Vanesa (2014)
We analyse different properties of the small-scale environment of Seyfert 2 for two samples selected according to the accretion rate parameter, R, from the Sloan Digital Sky Survey, Data Release 7 survey. We compare the results with two control samples of non-active galaxies that cover the same redshift range, luminosity, colours, morphology, age and stellar mass content. Our study shows that both high and low accretion rate subsamples reside in bluer and lower density environments than the control samples. However, we find that this difference is at least two times stronger for the low accretion rate Seyferts. In the vicinity of Seyfert 2, red galaxies have systematically lower values of stellar mass as compared with corresponding control samples. The lower values of stellar mass for red neighbours is more significant at higher density environments and it is more evident for low accretion rate Seyfert. We also find that this effect is independent of the host's stellar mass. Our results are consistent with a scenario where active galactic nucleus occurrence is higher in lower/medium density environments with a higher merger rate and a lack of a dense intergalactic medium (that can strip gas from these systems) that provide suitable conditions for the central black hole feeding. We find this particularly evident for the low accretion rate Seyferts that could compensate through the intergalactic medium the lack of gas of their hosts.